2017
DOI: 10.1111/acem.13181
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of History, Physical Examination, Laboratory Tests, and Point‐of‐care Ultrasound for Pediatric Acute Appendicitis in the Emergency Department: A Systematic Review and Meta‐analysis

Abstract: Presence of AA is more likely in patients with undifferentiated abdominal pain migrating to the RLQ or when cough/hop pain is present in the physical examination. Once AA is suspected, no single history, physical examination, laboratory finding, or score attained on PAS can eliminate the need for imaging studies. Operating characteristics of ED-POCUS are similar to those reported for RUS in literature for diagnosis of AA. In ED patients suspected of AA, a positive ED-POCUS is diagnostic and obviates the need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 125 publications
(325 reference statements)
5
116
1
10
Order By: Relevance
“…A CT examination is not as dependent on the operating technician; however it is not an optimal test due to radiation exposure. revealed that there is no single biomarker that can eliminate the need for further imaging studies [40].…”
Section: Discussionmentioning
confidence: 99%
“…A CT examination is not as dependent on the operating technician; however it is not an optimal test due to radiation exposure. revealed that there is no single biomarker that can eliminate the need for further imaging studies [40].…”
Section: Discussionmentioning
confidence: 99%
“…2 Si bien se han utilizado diferentes análisis de laboratorio y estudios por imágenes para llegar a un diagnóstico rápido y preciso, estos presentaban limitaciones a la hora de diferenciar la apendicitis de otras causas de dolor abdominal. 3 En el último tiempo ha habido un creciente interés en los parámetros hematológicos simples, como el volumen plaquetario medio (VPM) y el índice de plaquetas/linfocitos (IPL), que se cree que son marcadores de la gravedad de la respuesta inflamatoria sistémica. Durante el recuento de células sanguínea de rutina, los contadores hematológicos automatizados calculan y brindan recientes, se informó que la concentración de IVPML tiene implicancias clínicas en diferentes afecciones, como la inflamación sistémica, el infarto de miocardio y el compromiso de la circulación colateral coronaria.…”
Section: Introductionunclassified
“…Acute abdominal pain constitutes 20% of all pediatric surgery admissions [1]. Typical clinical presentation of appendicitis that includes pain, nausea, vomiting and low-grade fever sometimes accompanied by constipation or diarrhea may significantly differ in children [2]. A child may present with very few symptoms and in good general health or in very severe general condition with signs of septic shock and/or bowel obstruction.…”
Section: Introduction mentioning
confidence: 99%